1987
DOI: 10.1007/bf01728228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic omeprazole treatment on gastric endocrine function

Abstract: The influence of a 4-week treatment with the substituted benzimidazole omeprazole (20 mg daily) or placebo on gastric endocrine function was tested in healthy male volunteers. Compared with placebo-treated subjects basal serum gastrin levels were slightly but significantly increased after treatment with omeprazole from 10 to 22 pg/ml (medians; P less than 0.05) but returned to pretreatment values after 2 weeks recovery (9 pg/ml). Antral gastrin tissue concentration increased and was still elevated after recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Four to eight weeks' treatment with 20-90 mg omeprazole daily significantly increased basal serum gas trin levels in different groups of subjects [2,[27][28][29]. In most cases, these increases in plasma gastrin are moderate due to a feed back response to acid inhibition as in animal studies.…”
Section: Studies In Manmentioning
confidence: 78%
“…Four to eight weeks' treatment with 20-90 mg omeprazole daily significantly increased basal serum gas trin levels in different groups of subjects [2,[27][28][29]. In most cases, these increases in plasma gastrin are moderate due to a feed back response to acid inhibition as in animal studies.…”
Section: Studies In Manmentioning
confidence: 78%
“…43]. but the lower end of this range was reached in only I out of 30 patients with an intact stomach who were treated with omeprazole for 6-36 months [28]. Furthermore, pernicious anaemia had been diagnosed for a mean of 10.6 years before gas tric ECL-cell carcinoids were found in 5 out of 123 patients [II].…”
Section: Frestonmentioning
confidence: 99%
“…In man, increases are usually two-to three-fold (123,124). Unfortunately, the gastric inhibitory effects of omeprazole, and the circulating levels of gastrin, cannot be easily interpreted since the drug does not exert a graded dose-related effect on either of these indices of gastric function.…”
Section: Comparative Metabolism In Different Speciesmentioning
confidence: 97%
“…Thus it has been shown that omeprazole exerts what is almost an 'all-or-none' inhibitory effect on gastric secretion and gastrin release in man. For example, the currently 'recommended' dose is 20mg of omeprazole daily, a dose that inhibits gastric secretion in 5@70% of treated patients (118,(125)(126)(127) and increases gastrin levels in the same proportion (123). Unfortunately, no estimates of gastric secretion and gastrin release have been reported in the same individual patients.…”
Section: Comparative Metabolism In Different Speciesmentioning
confidence: 98%